Slow segmentation of faces in Autism Spectrum Disorder - van den Boomen, C.; Fahrenfort, J. J.; Snijders, T. M.; Kemner, C. (Elsevier Ltd, 2019)
Atypical visual segmentation, affecting object perception, might contribute to face processing problems in Autism Spectrum Disorder (ASD). The current study investigated impairments in visual segmentation of faces in ASD. Thirty participants (ASD: 16; Control: 14) viewed texture-defined faces, houses, and homogeneous images, while electroencephalographic and behavioral responses were recorded. The ASD group showed slower face-segmentation related brain activity and longer segmentation reaction times than the control group, but no difference in house-segmentation related activity or behavioral performance. Furthermore, individual differences in face-segmentation but not house-segmentation correlated with score on the Autism Quotient. Segmentation is thus selectively impaired for faces in ASD, and relates to the degree of ASD traits. Face segmentation relates to recurrent connectivity from the fusiform face area (FFA) to the visual cortex. These findings thus suggest that atypical connectivity from the FFA might contribute to delayed face processing in ASD.
Keywords: ASD; EEG; Face; Segregation